Pengaruh Peran dan Komitmen Manajer sebagai Internal Coach dalam Menerapkan Kepemimpinan Transformasional terhadap Kinerja Karyawan di PT. X - Pasti, Onma; Bangun, Wilson (DINASTI RESEARCH, 2025)
This study aims to analyze the impact of manager commitment in implementing transformational leadership styles through their role as coaches on improving team performance. One of the initiatives is the Leader as Coach program, where managers are trained as internal coaches to help teams achieve organizational goals. The research uses a quantitative methodology with a survey, involving 40 respondents, including managers as internal coaches and employees/coachees from various departments at PT. X who participated in the coaching program. Analysis is conducted using SmartPLS to test the relationship between the role and commitment of managers as internal coaches, transformational leadership style, and its impact on employee performance. Contextual factors such as managerial support, organizational structure, and organizational culture are also considered to assess their influence on the success and effectiveness of the coaching program in enhancing employee competencies and overall organizational performance.